INTERNATIONALIZATION OF AHLUSSUNNAH WAL-JAMA’AH IN SOUTHEAST ASIA: ANALYSIS OF THE DA’WAH MOVEMENT KH ALI TUNGKAL - Saidina Usman; Ris'an Rusli; Masyhur Masyhur; Makmur Harun (Akademika : Jurnal Pemikiran Islam, 2022)
The internationalization of Ahlussunnah Waljama'ah Islam in Southeast Asia in particular is growing rapidly. The spirit of maintaining the scientific sanad and teachings of Ahlussunnah Waljama'ah is one of the efforts to internationalize the role of KH Ali Tungkal's da'wah. With qualitative-descriptive and pure field research using bibliographical data methods, documentation, and interview results through a historical approach, this study explores: (1) The characteristics of the Islamic da'wah of Ahlussunnah Waljama'ah KH Ali Tungkal. (2) The Urgency of Internationalization of Ahlussunnah Waljama'ah Islam in Southeast Asia in a contemporary context with. The results of this study show that: (1) the characteristics of KH Ali Tungkal's missionary strategy movement, namely by establishing the Qadiriyah wa Naqsabandiyah (TQN) Tarekat. KH Ali Tungkal also founded the Al Baqiatus Shalihat Islamic boarding school. The characteristics of KH Ali Tungkal's da'wah material generally follow the Ahlussunnah Waljama'ah school. KH Ali Tungkal's da'wah material was planned as much as possible by referring to the books of Kifâyat al-Awwâm, Tuhfat al-Murȋd 'alâ Syarh Jauharat al-Tawhȋd, Syarh Hikam li 'Abdullâh al-Syarqâwȋ, Kifâyat al-Mubtadi'ȋn, Aqâ'id al -Faith and 'Charity Ma'rifah. The method of preaching KH Ali Tungkal both in the Al-Baqiyat Islamic Boarding School environment and in the community with Bil Lisan and Bil Qalam da'wah. (2) The internationalization of Ahlussunnah Waljama'ah Islam with tolerance, moderation, balance, and friendliness to all mankind is the most important thing in the context of Muslims in the contemporary era. So that KH Ali Tungkal's students are in Indonesia, Malaysia, Singapore, and Thailand. Internationalization and universalization of Islam Ahlussunnah Waljama'ah are increasingly unavoidable.